The reality of sustainable trade (London, 2000)
"The reality of sustainable trade is part of iied's"Stimulating Sustainable Trade series, which examines the impacts of social and environmental requirements on trade between the North and South and looks at how to encourage trade in more sustainable goods and services. ..."